2008
DOI: 10.3390/medicina44100094
|View full text |Cite
|
Sign up to set email alerts
|

Preventing chronic disease risk factors: Rationale and feasibility

Abstract: Objective. The majority of the mortality, morbidity, and disability in the United States and other developed countries is due to chronic diseases. These diseases could be prevented to a great extent with the elimination of four root causes: physical inactivity, poor nutrition, smoking, and hazardous drinking. The objective of this analysis was to determine whether efficacious risk factor prevention interventions exist and to examine the evidence that populationwide program implementation is justified. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…26 Controlling health risk behaviors, physical inactivity being one, is an important preventive practice that can substantially reduce morbidity and mortality from chronic disease. [27][28][29] Physical activity has been shown to be of particular priority among healthy behaviors; Well-Being Index national data indicate that regular exercise is more important to seniors' reported health status than is a healthy diet. 26 Consistent with many of the results of this study on SilverSneakers, the additional benefits seniors can gain from participating in regular moderate-intensity physical activity are wide ranging, including lowering the risk of depression, mitigating the development of disabilities, and improving the ability to do daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…26 Controlling health risk behaviors, physical inactivity being one, is an important preventive practice that can substantially reduce morbidity and mortality from chronic disease. [27][28][29] Physical activity has been shown to be of particular priority among healthy behaviors; Well-Being Index national data indicate that regular exercise is more important to seniors' reported health status than is a healthy diet. 26 Consistent with many of the results of this study on SilverSneakers, the additional benefits seniors can gain from participating in regular moderate-intensity physical activity are wide ranging, including lowering the risk of depression, mitigating the development of disabilities, and improving the ability to do daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that health professionals who have received training in preventive medicine tend to have healthier lifestyles and better attitudes toward preventive counseling [14,15]. Furthermore, studies have observed that counseling has a higher level of impact and effectiveness if the provider is a model of the messages transmitted to the patients [2,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Modifying these factors would reduce negative health outcomes [2][3][4][5][6], but such action requires intervention at different levels (political, social, community, individual) [7]. Behavioral interventions in clinical practice have been proven effective [8], and diverse models with which to implement these interventions have been established [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Both studies underline the necessity to encourage the general population's awareness of the consequences of unwholesome behaviors, in accordance with Njekela et al, who describe the prevalence of cardiovascular disease risk factors in a sample of men living in the urban area of Mwanza, Tanzania. Spreading information among the majority of the population is important, as the disease incidence can be reduced only by decreasing the mean level of risk factors among a large proportion of the population, and even interventions with a modest effect can largely impact the incidence rates when such interventions reach the entire population; clinicians, in turn, must reinforce the messages brought by prevention campaigns (Jordan et al 2008).…”
Section: Introductionmentioning
confidence: 99%